ANALISIS TANAH UNTUK REKOMENDASI PEMUPUKAN PADA BUDIDAYA JAGUNG, PADI DAN KETELA POHON - Bagus Sri Mulyanto; Supriyadi Supriyadi; Djoko Purnomo (Caraka Tani: Journal of Sustainable Agriculture, 2015)
The application of fertilization and giving organic matter of different causes differences in soil fertility status, with the availability of macro nutrients on a farm, then to know the action proper fertilization. The purpose of this study is to determine the dose fertilization fertility status of the local potential. The research was conducted using a survey method, ie by observing and sampling the soil directly in the field, followed by laboratory analysis to determine the chemical content of the soil. The results showed the level of soil fertility in Wonogiri low fertilizer needs are different in each district in Wonogiri. Areas with low nutrient availability will provide a high dose of fertilizer, and conversely a low fertilization results indicate the availability of nutrient elements in the soil are sufficient for plant growth, although it should still be nurtured to backup next season.